“Análisis Jurídico y Doctrinario de los Delitos Informáticos Tipificados en Colombia, Perú y Costa Rica para incorporarlos al Código Orgánico Integral Penal”. - Cabrera Vivar, Gabriel Alejandro (2024)
This research work entitled “Legal and doctrinal analysis of computer crimes classified in Colombia, Peru and Costa Rica to incorporate them into the Comprehensive Organic Criminal Code” addresses how foreign legislation classifies and punishes crimes that are committed through information and communication technologies, detecting among them the crimes that have not been studied in Ecuador. The objective of this legal and doctrinal study is how the crimes classified in the Colombian, Peruvian, and Costa Rican legislation vary in the names of the criminal type, classification of other conducts, characteristics, and specifications of the crimes, and penalties. They also resemble the definition and some elements of the crime found in the Ecuadorian legal system. In case a notable difference is reflected, it is proposed to adapt the different criminal types to our Comprehensive Organic Criminal Code, presenting a legal reform to support this problem. In its development, different methods and techniques were implemented. Surveys and interviews were carried out with legal professionals, computer specialists, and experts on the problem; in the same way, methods such as inductive, deductive, hermeneutic, and comparative were used; in addition, the results show that the lack of a classification of cybercrimes allows the impunity of certain behaviors that have not been taken into account by the legislator and these acts when reflected in the legal system, would allow the full exercise of the rights of citizens. Finally, the need for a reform to the Comprehensive Organic Criminal Code to incorporate these new crimes is highlighted. This work highlights the importance of taking urgent measures against this type of criminal behavior to avoid legal loopholes within the country's criminal system.